2011
DOI: 10.1007/s12325-011-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Update on adjuvant hormonal treatment of early breast cancer

Abstract: High-risk myelodysplastic syndromes present a poor prognosis, with survivals of close to only 1 year. The use of azacitidine, a DNA methyltransferase inhibitor, in this group of patients has transformed this grey image, with a demonstrated improvement in survival. Responses to survival are attained in a progressive manner, providing that the drug is used continually. This requires a good control of the adverse effects of the drug, which are primarily in the first cycles of treatment. The hematological adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Estrogen plays a crucial role in the progression of hormone-dependent breast cancer via the activation of estrogen receptors (ERs) encoded by ESR1 . By suppressing estrogen production, aromatase inhibitor (AI) treatments are essential parts of the therapeutic repertoire for ER + postmenopausal breast cancers [ 1 , 2 , 3 , 4 , 5 , 6 ]. Unexpectedly, several clinical trials have reported a therapeutic benefit of estrogen for AI-resistant advanced breast cancer [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen plays a crucial role in the progression of hormone-dependent breast cancer via the activation of estrogen receptors (ERs) encoded by ESR1 . By suppressing estrogen production, aromatase inhibitor (AI) treatments are essential parts of the therapeutic repertoire for ER + postmenopausal breast cancers [ 1 , 2 , 3 , 4 , 5 , 6 ]. Unexpectedly, several clinical trials have reported a therapeutic benefit of estrogen for AI-resistant advanced breast cancer [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery-specific and general pain were measured using an extended version of the Breast Cancer Pain Questionnaire (BCPQ) and Brief Pain Inventory (BPI), respectively. A Pain Severity Index (PSI) score was calculated using: PSI = Σ(Pain score at each site [0-10]) × (frequency [1][2][3][4][5]). 27 The BCPQ assessed the impact of surgical pain on physical activities relevant to the body area (physical impact of pain).…”
Section: Methodsmentioning
confidence: 99%
“…This phenotype was preserved across serially transplanted GS3 tumors (up to 14 passages so far). GS3 tumor pieces that were simultaneously transplanted with E2, showed no growth for half a year; meanwhile GS3 tumor pieces implanted alongside a placebo pellet (no E2) grew beyond 1000 mm 3 (Fig. 1b).…”
Section: E2 Treatment Inhibited the Proliferation Of Gs3 In Vivo And mentioning
confidence: 99%
“…S1c). After tumor volume reached approximately 200mm 3 , mice were randomized and implanted with an E2 (1 mg) or placebo pellet on their backside. These treatments lasted 7 days for experiments on single cell analysis and lasted 5 days, 10 days, 28 days, and 53 days for bulk RNA sequencing (RNAseq) experiments.…”
Section: In Vivo Animal Studymentioning
confidence: 99%
See 1 more Smart Citation